Persistent Rule-Following in the Face of Reversed Reinforcement Contingencies: The Differential Impact of Direct Versus Derived Rules. (November 2017) - Harte, Colin; Barnes-Holmes, Yvonne; Barnes-Holmes, Dermot; McEnteggart, Ciara
Rule-governed behavior and its role in generating insensitivity to direct contingencies of reinforcement have been implicated in human psychological suffering. In addition, the human capacity to engage in derived relational responding has also been used to explain specific human maladaptive behaviors, such as irrational fears. To date, however, very little research has attempted to integrate research on contingency insensitivity and derived relations. The current work sought to fill this gap. Across two experiments, participants received either a direct rule (Direct Rule Condition) or a rule that involved a novel derived relational response (Derived Rule Condition). Provision of a direct rule resulted in more persistent rule-following in the face of competing contingencies, but only when the opportunity to follow the reinforced rule beforehand was relatively protracted. Furthermore, only in the Direct Rule Condition were there significant correlations between rule-compliance and stress. A post hoc interpretation of the findings is provided.